Tolerant Worldview and Deradicalism in Pesantren: Case of Pesantren Al-Baqiyatush Shalihat Tanjung Jabung Barat, Jambi - Badarussyamsi Badarussyamsi; Fathul Anwar; Shofiyullah Muzammil; Ermawati Ermawati (UIN Sunan Kalijaga Yogyakarta, 2021)
This article examines the role of Al-Baqiyatush Shalihat Tanjung Jabung Barat—Islamic Jambi's (Boarding School) Pesantren in promoting tolerance and deterring radicalism. When the surrounding environment is so plural with many religions other than Islam, this pesantren remains true to the principles of tolerance and is not fanatical. When the region around the pesantren drew public attention as a hotbed of radicalism and terrorism, the pesantren continued to instill kindness, anti-radicalism, and anti-terrorism. In the fight against radicalism and terrorism, this pesantren collaborates with the local government. In this article, the major question is how the pesantren strategy instills tolerance values in efforts to deradicalize or counter-terrorism acts. The research relied heavily on observation, which was supplemented by interviews with Kyai and Ustadz, students, and neighbors in the vicinity of the pesantren. The Pesantren Al-Baqiyatush Shalihat, according to this study, has the natural ability to oppose radicalism through the use of the Pesantren Al-Baqiyatush Shalihat.